From Work Environment to the Decision to Stay: The Central Role of Work Life Balance in Health Workers at Maternity and Children Hospital - Christin; Reza Hilmy; Nofierni (Universitas KH. Abdul Chalim Mojokerto, 2026)
The high turnover rate (18–25%) of health workers in Indonesian private hospitals encourages the need for more effective retention strategies. This phenomenon occurred at RSIA Type C North Jakarta, which is experiencing a management transition and organizational change in 2023, so that it has the potential to change the work environment, work engagement, and work-life balance of employees. Intention to stay depends not only on a good work environment and high work engagement, but rather on the organization's ability to convert both factors into a sustainable work-life balance. This study aims to analyze the influence of work environment and work engagement on the Intention to Stay of health workers, with work-life balance as a mediator variable. Using a quantitative approach and survey method on the population of health workers in the hospital, this study tested the mediation model through path analysis. The findings of the study are expected to provide strategic recommendations for hospital management to improve retention through interventions that strengthen work-life balance. The method used was a quantitative approach based on a cross-sectional survey of 137 clinical and non-clinical workforces, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the model was able to explain 57.9% of the variation in Intention to Stay and 15.4% of the variation in work-life balance. Work-life balance was the strongest predictor of Intention to Stay (β = 0.538), followed by work environment (β = 0.293) and work engagement (β = 0.124). Indirect influence is also significant through work-life balance mediation. All constructs showed good validity and reliability, while the structural model was declared feasible with a GoF of 0.467. These findings confirm the importance of strengthening psychosocial factors in health worker retention strategies in hospitals.